Clinical and Neurocognitive Predictors of Functional Outcome in Depressed Patients with Partial Response to Treatment: One Year Follow-Up Study - Castellano S (Dove Medical Press, 2020)
Sabrina Castellano,1 Carla Torrent,2 Maria Cristina Petralia,3 Justyna Godos,4 Rita Anna Cantarella,5 Andrea Ventimiglia,6 Simona De Vivo,6 Silvia Platania,1 Maria Guarnera,7 Concetta Pirrone,1 Filippo Drago,4 Eduard Vieta,2 Santo Di Nuovo,1 Dina Popovic,2,8,* Filippo Caraci4,9,* 1Department of Educational Sciences, University of Catania, Catania, Italy; 2Barcelona Bipolar Disorders Program, Institute of Neurosciences, University of Barcelona, IDIBAPS, CIBERSAM, Barcelona, Catalonia, Spain; 3IRCCS Centro Neurolesi Bonino Pulejo, Messina, Italy; 4Oasi Research Institute-IRCCS, Troina 94018, Italy; 5Department of Mental Health, ASP3 Catania, Catania, Italy; 6Villa dei Gerani Clinic ASP3 Catania, Catania, Italy; 7Faculty of Human and Social Sciences, University of Enna “KORE”, Enna, Italy; 8Bipolar Disorders Program, Sheba Medical Center, Ramat Gan, Israel; 9Department of Drug Sciences, University of Catania, Catania, Italy*These authors contributed equally to this workCorrespondence: Sabrina CastellanoDepartment of Educational Sciences, University of Catania, Via Ofelia 1, Catania 95124, ItalyTel +39 0952508060Fax +39 0952508070Email sabrina.castellano@unict.itBackground: Cognitive dysfunction represents a distinct biological and clinical dimension in major depression disorders (MDD) and cognitive performance strongly affects psychosocial functioning in patients diagnosed with MDD.Objective: To assess which neurocognitive variables at baseline predict the functional outcome of MDD patients in a 1-year follow-up study as assessed by Functioning Assessment Short Test (FAST) and whether the improvement observed on affective and cognitive symptoms in our 12 week-prospective observational study after treatment with selective serotonin reuptake inhibitors (SSRIs) and selective noradrenalin reuptake inhibitors (SNRIs) can affect the following long-term psychosocial functional outcome at 1 year in the same MDD patients.Methods: We recruited a total of 31 patients (8 males; 23 females) with MDD who had previously completed a pharmacological treatment with SSRIs (n = 22) or SNRIs (n =  9) for 12 weeks, and then continued the same pharmacological treatment for 1 year. After an average 1-year follow-up, they were interviewed with the FAST to assess functional outcome. Multivariate analyses were applied to identify clinical and neurocognitive predictors of functional outcome.Results: Total Montreal Cognitive Assessment (MoCA), Digit Span forward (Span F) and backward (Span B), and 15 Rey words immediate recall (Rey I) scores significantly correlated with FAST. However, after performing regression models only Rey immediate recall score was useful to predict long-term functional outcome (Pearson correlation coefficient R= − 0.68, p <  0.001) in four specific subdomains of FAST. When considering changes in affective and cognitive symptoms at the end of the 12 weeks of pharmacological treatment with SSRI or SNRIs (T1-T0) by multiple regression analysis, we found that Span F-test predicted scores in the FAST leisure domain, whereas, changes in Span F, Frontal Assessment Battery (FAB) and Rey I predicted psychosocial functioning in the specific “cognitive” subdomains of FAST.Conclusion: Our data suggest that long-term psychosocial functioning can be influenced by neurocognitive performance at baseline, with verbal memory playing a key role in overall functioning. Furthermore, improvement in verbal memory can predict functional outcome at one year in MDD patients with a recent history of partial response to antidepressants.Keywords: major depression, SSRI, SNRI, cognition, psychometric tools, antidepressant drugs